1990
DOI: 10.1128/jb.172.2.922-931.1990
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequencing and characterization of Pseudomonas putida catR: a positive regulator of the catBC operon is a member of the LysR family

Abstract: Pseudomonas putida utilizes the catBC operon for growth on benzoate as a sole carbon source. This operon is positively regulated by the CatR protein, which is encoded from a gene divergently oriented from the catBC operon. The catR gene encodes a 32.2-kilodalton polypeptide that binds to the catBC promoter region in the presence or absence of the inducer cis-cis-muconate, as shown by gel retardation studies. However, the inducer is required for transcriptional activation of the catBC operon. The catR promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 52 publications
1
92
0
1
Order By: Relevance
“…Its deduced amino acid sequence shares high identity with LysR-type transcriptional regulators involved in benzoate or catechol catabolism such as ORF R# (55 %) of one of the two catechol gene clusters of Frateuria sp. ANA-18 (Murakami et al, 1999), catR of P. putida PRS2000 (50 %) (Houghton et al, 1995) and RB1 (48 %) (Rothmel et al, 1990), and benM (48 %) and catM (45 %) of ADP1 (Collier et al, 1998 ;RomeroArroyo et al, 1995). NK8 ORF4 was named cbeR because subsequent results showed that the gene is involved in (chloro)benzoate catabolism, and that it responds to 3CB, 4CB and benzoate, as well as cis,cismuconate.…”
Section: Cloning and Sequencing Of The Chlorobenzoate Dioxygenase Genesmentioning
confidence: 99%
“…Its deduced amino acid sequence shares high identity with LysR-type transcriptional regulators involved in benzoate or catechol catabolism such as ORF R# (55 %) of one of the two catechol gene clusters of Frateuria sp. ANA-18 (Murakami et al, 1999), catR of P. putida PRS2000 (50 %) (Houghton et al, 1995) and RB1 (48 %) (Rothmel et al, 1990), and benM (48 %) and catM (45 %) of ADP1 (Collier et al, 1998 ;RomeroArroyo et al, 1995). NK8 ORF4 was named cbeR because subsequent results showed that the gene is involved in (chloro)benzoate catabolism, and that it responds to 3CB, 4CB and benzoate, as well as cis,cismuconate.…”
Section: Cloning and Sequencing Of The Chlorobenzoate Dioxygenase Genesmentioning
confidence: 99%
“…1a) is introduced into a P. putida strain which is normally incapable of utilizing phenol, the bacteria acquire the ability to degrade phenol via the chromosomal cat pathway encoding catechol degradation in concert with the phenol to catechol or CCM conversion mediated by the pheBA operon (Kasak et al, 1993). Transcription of the chromosomal ortho pathway genes catBCA and of the plasmid-encoded pheBA operon is activated by the same positive regulator, the chromosomally encoded LysR family protein CatR (Kasak et al, 1993 ;Rothmel et al, 1990). Despite the different origins of the catBCA and the pheBA promoters, the CatR-dependent transcriptional activation mechanism of these promoters seems to be similar.…”
Section: Ipmentioning
confidence: 99%
“…Mutational analysis of the pheBA promoter (Franz & Chakrabarty, 1987) and tcbCDEF (van der Meer et al, 1991), have been characterized in bacteria capable of degrading chlorocatechols and are located on catabolic plasmids. Transcription of the catBCA, clcABD and tcbCDEF operons is controlled by the regulatory proteins CatR (Rothmel et al, 1990), ClcR (Coco et al, 1993) and TcbR (van der Meer et al, 1991), respectively. These activators belong to the LysR family of bacterial regulators and utilize similar mechanisms for activating transcription (McFall et al, 1997(McFall et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…The catBCA operon encodes three enzymes of the ortho-pathway required for benzoate catabolism, namely muconate lactonizing enzyme I, muconolactone isomerase and catechol 1,2-dioxygenase, respectively (Houghton et al, 1995). The induction of this operon, which is σ&%-independent, requires a LysR family transcriptional activator, CatR, and an inducer molecule, cis,cis-muconate (CCM), an intermediate of the ortho-pathway (Rothmel et al, 1990(Rothmel et al, , 1991. The pheB and pheA genes originating from plasmid DNA of Pseudomonas sp.…”
Section: Abbreviationsmentioning
confidence: 99%